Prolapse in pregnancy: a case report - Hock, Sarah Van Der; Seth, Ishith; Hapangama, Nipuni; Cuomo, Roberto; Dhupar, Nita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pelvic organ prolapse in pregnancy is uncommon. It poses unique maternal and foetal risks which must be carefully managed in the antepartum, intrapartum, and post-partum period. This case series and literature review discusses two cases of young female patients without significant risk factors presenting in their third trimester of pregnancy with symptoms of pelvic organ prolapse (POP). Both patients were treated conservatively and went on to have an uncomplicated vaginal delivery at term. These cases highlight the need for routine pelvic floor assessments in the antenatal period to detect the early signs of POP. The ensuing literature review provides updated insights into the predisposing factors, diagnosis, and management of POP, including the importance of managing the psychosocial implications of the condition.